The Effect of Teams Games Tournament (TGT) on Students’ Motivation, Engagement, and Mathematics Performance - Sukowati, Kukuh; Suyanto, Adi; Noviyanti, Mery (Indonesian Journal of Mathematics Education, 2024)
This study aims to analyze the impact of implementation the Teams Games Tournament (TGT) model on students’ learning motivation, learning engagement, and mathematics learning outcomes in partially and simultaneously. This research employed a quantitative approach. The population consisted of all fifth-grade students in elementary schools in Kebumen District, totaling 1,664 students. A sample of 255 students was selected using a simple random sampling technique. Data were collected through observation, questionnaires, and documentation. The hypotheses were tested using non-parametric statistical methods, including the Wilcoxon Signed Rank Test, Mann Whitney Test, and Median Test. The results showed that: (1) there was a positive impact of the implementation of TGT on learning motivation, engagement, and mathematics learning outcomes in elementary school students as indicated by the Wilcoxon Signed Rank Test significance value of 0.000; and (2) simultaneously, the implementation of the TGT model also had a significant effect on students’ motivation, activeness, and mathematics learning outcomes, with a p-value of 0.000. Based on these findings, it is recommended that teachers apply the TGT model as an alternative strategy to enhance student motivation, engagement, and academic performance in mathematics learning. Further research may explore the integration of TGT with digital learning media or its long-term effects on students’ cognitive and social development.